Planimetry of the Monumental of Jaén Kingdom´s “Caudillos” located in Santisteban del Puerto - Sánchez-González, Antonio (Revista de Estudios Andaluces, 2020)
The Ducal Archive of Medinaceli hosts an interesting collection of maps and plans which has recently been catalogued by a team of specialists during the completion of an I+D research project. In the collection, there is a set of plans associated with the Casa de Santisteban del Puerto, the so-called Caudillos mayores(main chieftains) of the Kingdom of Jaén. In this paper, we will be focusing on the most relevant properties in this city: the famous Castle of San Esteban, the Ducal Palace and the Convent of San Francisco. Our research is based on a descriptive methodology on the main urban-planimetric typological characteristics of historical cities, as is the case of Santisteban del Puerto. And its result not only provides the opportunity to make a reflection about the importance of drawing in the world or architecture, but also rectifies some imprecisions concerning this catalogue in order to reach a better understanding of the maps. The importance of the planimetry covered here lies in the fact that the monuments no longer exist.